Theory of free-carrier absorption in the presence of a quantizing magnetic field in quasi-one-dimensional quantum well structures - Ibragimov, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The theory of free-carrier absorption is given for a quasi one-dimensional
semiconducting structures in a quantizing magnetic field for the case when carriers are scattered
by polar optical phonons and acoustic phonons and the radiation field is polarized
perpendicular to the magnetic field direction.